Моделювання пористої і зеренної структур при двостадійному спіканні надтвердих PCBN систем cBN – Al, cBN – TiB2 (TiN) – Al - Коновал, С.М.; Гарбуз, Т.О.; Беженар, М.П.; Божко, С.А.; Нагорний, П.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The experimentally-rated method of modeling of porous and grain structures of cubic boron nitride composites, which obtain by reactionary sintering with preimpregnation by aluminium under pressure is proposed. Possibility of process control of aluminium dispersing in a mixture at an impregnation stage under pressure is shown.